Determinan Pelayanan Pendaftaran Terhadap Kepuasan Pasien BPJS Dan Pasien Umum Di RSU Sari Mutiara Lubuk Pakam Tahun 2022 - Liem, John Barker; Haruman, Sakinah Tasya; Karo-Karo, Siddik (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
The level of patient statisfication is considered as one of the most important dimensions of quality and is one of the main indicators of the standard of a health facility which is the result of the influence of health services on the hospital. This study aims to determine the Determinats of Registration Services for BPJS Outpatients and General Patients at Sari Mutiara Lubuk Pakam Hospital in 2022. This study uses a quantitative method, with apopulation is unknown and the sample of 96 people is then rounded up to 100 people. The data were analyzed using Chi-Square test statistics to determine differences in the level of statistification of BPJS and General patients with the registration service of Sari Mutiara Hospital. Lubuk Pakam 2022. Based on the results of the study, it was found that the statisfication of BPJS patients who chose very satisfied 25 people 64.1% satisfied 22 people 50.0% quite satisfied 2 people 14.3% dissatisfied 1 person 33.3% and in General petients who chose very satisfied 14 people 35.9% satisfied 22 people 50.0% quite satisfied 12 people 85.7% dissatisfied 2 people 66.7%. Based on the results of statistical test p value of 0.014 which shows that there are differences in the level of statisfication of BPJS patients and Public Services at Sari Mutiara Lubuk Pakam Hospital in 2022.